Clinical and epidemiological aspects of rabies in the province of Cienfuegos. 2016-2017 - Sahily de la Caridad Ortega Medina; Tamara Montenegro Calderón; Maydel Llull Díaz; Lisamary López Ortega; Idalmis Reyes Rodríguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Foundation: rabies is a viral disease with a mortality of almost 100%, but avoidable by vaccination. Objective: To describe clinical and epidemiological aspects of rabies in the province of Cienfuegos, in the years 2016 and 2017. Methods: retrospective descriptive study of all the patients injured by animals in the province of Cienfuegos, during the period from January 2016 to December 2017. The variables analyzed were: municipalities of occurrence, injury severity, age groups, type of animal injury, rabies treatment, canine sanitation and rabies surveillance. The primary source for obtaining the information was injured patient´s notification cards review in the health areas of the Cienfuegos Province and data from the Department of Statistics of the Provincial Center for Hygiene Epidemiology and Microbiology of Cienfuegos. Results: 2 577 injured were reported; Lajas was the municipality with the highest number of reports in 2016 and Palmira in 2017; the risk of humans to get rabies is kept high; 87.5% of the injuries were produced by canines, of which 35.2% are street dogs. The 5-9 years pediatric ages have the highest rates; slight injuries predominated and sanitation activity was higher in 2017. Conclusion: there are still difficulties in the prevention and control of rabies, so it is important to work on the deficiencies to avoid the occurrence of cases taking into account the high lethality of this disease.